Open season 2 [videorecording (DVD)] - O'Callaghan, Matthew; Wilderman, Todd; McHale, Joel, 1971-; Glover, Crispin; Krakowski, Jane; Epps, Mike; Hack, Olivia; Schirripa, Steven R. (Sony Pictures Home Entertainment, 2009)
Elliot and Boog find themselves on another adventure. After falling head over hooves in love with Giselle, Elliot's road to the alter takes a slight detour when Mr. Weenie is kidnapped by a group of pampered pets determined to return him to his owners. Boog, Elliot, McSquizzy, Buddy and the rest of the woodland creatures launch a full-scale rescue mission for their sausage-shaped friend and soon find themselves in enemy camp. Led by a toy poodle named Fifi, the pets do not plan to let Mr. Weenie go without a fight.